Comparing the effectiveness of topical fluticasone 0.05% cream versus topical tacrolimus 0.1% ointment in pediatric atopic dermatitis: A randomized controlled trial - Sanjeev Handa; Ariganesh Chandrasegaran; Amrinder Jit Kanwar; Rahul Mahajan (Wolters Kluwer Medknow Publications, 2022)
Background: There is sparsity of data on the comparative effectiveness of topical steroids and topical tacrolimus in the treatment of pediatric atopic dermatitis (AD) and prevention of its relapse. Materials and Methods: Fifty eligible pediatric AD patients (with an objective SCORAD >40) were included in the study and were randomized into two groups of 25-those receiving topical fluticasone 0.05% cream twice daily and those receiving topical 0.1% tacrolimus ointment twice daily. All the patients were assessed at baseline and weeks 2, 4, and 6. At week 6, patients achieving >75% improvement were put on maintenance therapy of thrice weekly application of the respective drugs in each group and the patients were followed up at 10 and 14 weeks to observe for any flare of the disease. Results: The two treatment groups were similar at baseline. In the fluticasone group, 21 out of 25 patients (84%) achieved >75% improvement in SCORAD, while in the tacrolimus group, 17 out 25 patients (68%) achieved >75% improvement; P = 0.185]. Complete remission (100% improvement) was seen in 16 patients (64%) in the fluticasone group compared to 13 patients (52%) in the tacrolimus group at the end of 6 weeks (P = 0.38). The mean SCORAD values at 2, 4, and 6 weeks were compared between the 2 groups. The number of relapses was 1 in each group among patients on maintenance treatment. Conclusion: Both fluticasone cream and tacrolimus ointment are effective and safe for treatment of childhood AD, and for the prevention of AD flares.